Children as potential – a window to cultural ideals, anxieties and conflicts. Issue 3 (4th May 2022) - Gilliam, Laura; Gulløv, Eva
ABSTRACT: Drawing on sociologist Norbert Elias' theory of civilising processes, this article argues for a perspective on children as 'potential'. With this notion, we focus on the efforts, hopes and fears that adult society invest in children and through them in future society. Seeing this investment as a result of historical processes and social dynamics, we hold that the perspective of children as potential provides a window to deep-felt ideals and anxieties in society, the norms of civilised society that are established as well as the ongoing struggles about these norms. In this way, studying investments in children are particularly significant for social science. Yet, as cultural norms have to pass through the transformative world of childhood to be reproduced, we also have to explore how children actively affect the outcome of the civilising projects and the processes of continuity and change.